A Novel Compact MIMO Planar Inverted-F Antenna (PIFA) for Future 5G Wireless Devices - Loharia, Neha; B. Rana, Shashi; Kumar, Naveen (International Journal of Engineering and Technology, 2018)
In the last decade, mobile communication has shown a tremendous growth in various categories of wireless communication. A novel miniature MIMO Planar inverted F Antenna (PIFA) for 5G future communication has been presented in this paper as a MIMO antenna working at 10 GHz band is not available in recent literature. The proposed PIFA has low profile structure with two radiating elements on its opposite edges. The proposed 5G frequency band of 10 GHz is covered by the MIMO antenna. Various antenna & MIMO performance parameters such as isolation, return loss, VSWR, diversity gain, ECC and radiation pattern are also presented and discussed. Simulated and measured results are in good match with each other.